The Design of Augmented Reality-Based Synectic Model Device in Writing Short Stories - Damayanti, Deasy Aditya; Nurwahidah, Lina Siti; Hamdani, Agus; Hasim, Abdul (MEDIASI, 2021)
Â A Short story is a miniature of people's experience while the characters, plot, and setting aim to record imaginative events (Stanton, 2017). When making up story ideas, students have problems developing story facts such as plot, characters, and settings (Sayuti, 2006). This barrier emerged conflicts that were unevenly distributed across all stages of the course. The direct characterization employed in storytelling made the short stories less varied. The physical and setting depicted did not work out optimally. The advantage of using the synectic model is that it can allow students to look for and makeup concepts to describe objects through an analogy process. Augmented Reality allows users to interact with an object's interface and see it in a well-designed and attractive 3D format, so it can solve student difficulties in developing story ideas in writing short stories.